2005
DOI: 10.1017/s0950268805004899
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of reportedCampylobacterinfection in England, 1989–1999

Abstract: SUMMARYCampylobacter is the most common bacterial cause of gastroenteritis in England and Wales, with 45 000 cases reported annually. Campylobacter incidence is highly seasonal ; the consistent peak in late spring suggests a role for meteorological factors in the epidemiology of this organism. We investigated the relationship between ambient temperature and Campylobacter enteritis using time-series analysis to study short-term associations between temperature and number of Campylobacter reports adjusted for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 29 publications
12
57
2
4
Order By: Relevance
“…We cannot claim that our study proves an absolute seasonality pattern of Campylobacter; rather, it indicates a possible peak in the so-called warm months resembling those indicated in other European countries (32,34,40). In our study, the number of samples varied over months for logistical reasons.…”
Section: Discussionmentioning
confidence: 61%
“…We cannot claim that our study proves an absolute seasonality pattern of Campylobacter; rather, it indicates a possible peak in the so-called warm months resembling those indicated in other European countries (32,34,40). In our study, the number of samples varied over months for logistical reasons.…”
Section: Discussionmentioning
confidence: 61%
“…The reasons for the seasonal variation are not fully understood but are likely to involve the frequency and nature of exposure of the flocks to Campylobacter spp. There is further evidence that climatic factors such as temperature correlate with both broiler flock and human infections (36,43,52). Temperature could also affect the environmental sources of Campylobacter spp.…”
mentioning
confidence: 99%
“…The relationship between enteric infections and environmental temperature has been studied in Europe (Kovats et al, 2004(Kovats et al, , 2005Tam et al, 2006;Bentham and Langford, 2001), Australia (D'Souza et al, 2004;Bi et al, 2008;, the USA (Curriero et al, 2001), Canada (Fleury et al, 2006), and Asia . Most of these studies indicated that there was a positive association between temperature and enteric infections such as Salmonella infections and Campylobacter infections as well as Bacillary Dysentery.…”
Section: Infectious Diseases and Human Population Healthmentioning
confidence: 99%